P141 Let's think twice before abandoning secondary cytoreductive surgery in recurrent ovarian cancer. (1st November 2019) - Marchetti, C; Rosati, A; Scaletta, G; Pietragalla, A; Arcieri, M; Ergasti, R; Palluzzi, E; Scambia, G; Fagotti, A
Abstract : Introduction/Background: The role of secondary cytoreductive surgery (SCS) in recurrent ovarian cancer (ROC) is controversial after results of randomized trials. The aim of this study is to evaluate SCS in ROC patients with BRCA ½ (BRCAmut) who received platinum-based chemotherapy followed by olaparib maintenance. Methodology: This is a case-control study. Patients with recurrent platinum-sensitive high grade serous ovarian cancer admitted to our Gynecologic Oncology Unit between 2014 and 2018 were identified. Main eligibility criteria were positive BRCA 1/2 germline or somatic mutation status and olaparib maintenance at primary recurrence after response to platinum based chemotherapy. Cases were those who received SCS followed by medical treatment (SCS-CT-OLA, group 1), controls were those who received medical treatment alone (CT-OLA, group 2). Results: Overall, 47 patients were identified; 24 (51%) BRCAmut women undergoing SCS followed by platinum based chemotherapy and olaparib maintenance were matched with 23 (49%) BRCAmut women who received medical treatment alone. Groups were well balanced: no statistical differences were found with regard of age, mutational status, outcomes and treatment's approach at diagnosis, timing and patterns of disease presentation at recurrence (table 1 and 2). Median time to first subsequent therapy (TFST) was significantly longer in the SCS-CT-OLA than in the CT-OLA group (42 months vs 16 months; p=0.05; figure 1). Furthermore, SCS-CT-OLA patients had the best post-recurrence survival (PRS), with a 3-year PRS of 81% in SCS-CT-OLA group versus 43% in CT-OLA group (p=0.01). Conclusion: SCS increases TFST and PRS in ROC patients with BRCAmut candidate for olaparib maintenance after platinum-based chemotherapy. Prospective studies are needed. In the era of personalized medicine, indication to SCS should be individualized. Disclosure: Nothing to disclose.